Haemodynamic Variations of Flow to Renal Arteries in Custom-Made and Pivot Branch Fenestrated Endografting. (January 2017) - Ou, J.; Tang, A.Y.S.; Chiu, T.L.; Chow, K.W.; Chan, Y.C.; Cheng, S.W.K.
Abstract : Objective: This study aimed to investigate variation of blood flow to renal arteries in custom-made and pivot branch (p-branch) fenestrated endografting, using a computational fluid dynamics (CFD) technique. Methods: Idealised models of custom-made and p-branch fenestrated grafting were constructed on a basis of a 26 mm stent graft. The custom-made fenestration was designed with a 6 mm diameter, while the 5 mm depth renal p-branch was created with a 6 mm inner and 15 mm outer fenestration. Two configurations (option A and option B) were constructed with different locations of p-branches. Option A had both renal p-branches at the same level, whereas option B contained two staggered p-branches at lower positions. The longitudinal stent orientation in both custom-made and p-branch models was represented by a takeoff angle (ToA) between the renal stent and distal stent graft centreline, varying from 55° to 125°. Computational simulations were performed with realistic boundary conditions governing the blood flow. Results: In both custom-made and p-branch fenestrated models, the flow rate and wall shear stress (WSS) were generally higher and recirculation zones were smaller when the renal stent faced caudally. In custom-made models, the highest flow rate (0.390 L/min) was detected at 70° ToA and maximum WSS on vessel segment (16.8 Pa) was attained at 55° ToA. In p-branch models, option A and option B displayed no haemodynamic differences when having the same ToA. The highest flow rate (0.378 L/min) and maximum WSS on vessel segment (16.7 Pa) were both calculated at 55° ToA. The largest and smallest recirculation zones occurred at 90° and 55° ToA respectively in both custom-made and p-branch models. Custom-made fenestrated models exhibited consistently higher flow rate and shear stress and smaller recirculation zones in renal arteries than p-branch models at the same ToA. Conclusions: Navigating the renal stents towards caudal orientation can achieve better haemodynamic outcomes in both fenestrated devices. Custom-made fenestrated stent grafts are the preferred choice for elective patients. Further clinical evidence is required to validate the computational simulations.